Predicting market risk with density combination: An introduction - Ardia, David; Kolly, Jeremy (My University, 2016)
Density forecast combination is a useful tool for risk managers to reduce model risk. We present up-to-date methodologies in the field, discuss key issues and provide some illustrations.
Keywords: Density forecast combination; censoring; incomplete model set; risk model contribution; skew Student-t distribution; pool risk forecasts